Cryptosporidium parvum parasite microscopic and molecular diagnostics in the Holy Karbala/ Iraq . (Journal of Pharmaceutical Negative Results, 2022)
The present study aimed to diagnose the Cryptosporidium parasite and identify the extent of the parasite’s spread in people who sufferfrom diarrhea and its relationship to epidemiological factors in the holy Karbala Province using three different diagnostic methods.Microscopic examination, which includes staining the samples with the modified acid dye, as well as using the molecular examinationusing the technique of polymerase chain reaction, the collection of samples was carried out in Al-Hussein Medical City and KarbalaTeaching Hospital for children. So, in the laboratories of the College of Veterinary Medicine at the University of Karbala for the periodfrom the beginning of September 2020 until the end of February 2021, 320 stool samples were collected from persons suspected ofhaving the parasite (those with diarrhea and not infected) and who came to Imam Hussein Medical City and Karbala Teaching Hospital.For children, of both sexes, and with age groups from (1-50) years, this was done. The first half of each sample was utilized to producereasonably thick smears for evaluation with the modified acid dye, and the second part was preserved at -20°C for subsequent use inthe molecular study., as the results of the microscopic examination using the modified acid dye showed that the number of infectedsamples reached 26 samples as the number of Males have 15 samples, while the number of females reached 11 samples and the overallinfection rate was 8.1%, while the infection rate was lower by using immunological tests by 6.8%.The incidence rate was affected by epidemiological factors below the probability level P≤ 0.05, as males recorded a higher rate ofinfection compared to females, as the infection rate reached 10% and 6.47%, respectively, while the infection rate recorded significantdifferences according to the type of housing, as the infection rate reached 12.2% in the countryside and in The city, the infection ratewas 6.5%. As the current study recorded different infection rates according to the months of the year, the highest rate of infection wasin the month of December by 16%, while the lowest injury rate was concentrated in the month of October and November by 1.8%,4.7%, and the study recorded. The highest rate of infection was in the age group (1-10) by 14.1%, while the current study did not recordany infection in the age group (40-31). Drinking water sources played a role in the spread of the Cryptosporidium parasite, the infectionrate for persons who drink tap water was 18.9%, whereas the lowest rate for people who drink sterile water was 4.8 percent, accordingto the research. As for the companion parasites, the current study recorded that the most associated parasite is Entamoeba histolyticaby 3.4%, while the appearance of Girdia lamblia parasite was less by 2.1%.A molecular assay was used on the second part of the samples, which was kept at a temperature of -20, for the purpose of confirminginfection in the positive samples and others, and to determine the accurate diagnosis of this parasite. Specific primers for the oocystwall protein (COWP) gene were used, Cryptosporidium oocyst wall protein. Polymerization, the first stage was the polymerase chainreaction (PCR), where the DNA was amplified using specific primers and the reaction was accomplished using a thermocycler andunder optimal conditions. The results revealed a single package (Singal band in agarose gel) with weight Molecular 769 base pairs ofnitrogenous bases in the DNA extracted from stool samples of people with Cryptosporidium, which is an indication of the patient'sinfection with the parasite, and the second stage in which the technique of nested polymerase chain reaction is used. By using two typesof specific primers in the reaction (COWP F and COWP R), the DNA was amplified using specific primers and it was The reactionwas carried out using a thermocycler device and under optimal conditions, the results showed the presence of one packet in the acarosegel with a molecular weight of 553 pairs of nitrogenous bases in the DNA extracted from the stool samples of people withCryptosporidium, an indication of the patient's infection with the parasite, and the current study showed that the sensitivity Themicroscopy examination was less than the molecular examination, It was concluded from this study that the Cryptosporidium parasiteis one of the parasites that cause diarrhea in humans, especially children in Karbala Province. It may be diagnosed using a variety ofways, with the polymerase chain reaction approach being one of the most effective.